Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2340/00015555-0666
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Acanthosis Nigricans with Enhanced Expression of Fibroblast Growth Factor Receptor 3

Abstract: Letters to the Editor 435 since 1990 have reported the use of terlipressin for the treatment of HRS with good outcomes and low risk of adverse effects. Incidence of secondary ischaemic events in HRS differs depending on series from 5% to 29% (1. 2, 8, 9). Significantly, a recent meta-analysis revealed that no permanent interruption of terlipressin was needed because of intolerance ( I ).Undesirable effects are usually mild and disappear by lowering the dose of the drug. i.e. paleness, acral cyanosis, abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…TGF-alpha is a primary mediator of benign and malignant keratinocyte hyperproliferation in vivo (58). Some authors speculate that activation of fi broblast growth factor receptor 3 (FGFR3) might have some relevance to the formation of MAN (59). Simultaneous activation of epidermal growth factor receptor 3 (EGFR3), insulin-like growth factor--1 (IGF-1) and melanocyte stimulating hormone  ; a systemic immunologic response to the primary tumor as a cause cannot be discarded (13).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-alpha is a primary mediator of benign and malignant keratinocyte hyperproliferation in vivo (58). Some authors speculate that activation of fi broblast growth factor receptor 3 (FGFR3) might have some relevance to the formation of MAN (59). Simultaneous activation of epidermal growth factor receptor 3 (EGFR3), insulin-like growth factor--1 (IGF-1) and melanocyte stimulating hormone  ; a systemic immunologic response to the primary tumor as a cause cannot be discarded (13).…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary diseases associated with AN demonstrate activating germ line mutations in the fibroblast growth factor receptor 3 (FGFR3) gene, which increase keratinocyte growth [1821]. A positive association of FGFR3 expression has been reported in two cases of malignant AN, with expression throughout the acanthotic lesions [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Hida et al also reported the possible role of fibroblast growth factor receptor 3 (FGFR3) in the etiopathogenesis of ANM. 16 The case reported here, with typical lesions of acanthosis nigricans maligna, florid cutaneous papillomatosis and tripe palms occurred in the absence of any gastrointestinal complaint. Since gastric adenocarcinoma is the most common neoplasia associated with these paraneoplastic dermatoses, supplementary diagnostic tests were performed and a malignant gastric tumor was confirmed, already with distant lung metastases and regional lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%